2022
DOI: 10.1021/acs.energyfuels.2c01392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Valence State in Co-Based Cocatalyst on the Photocatalytic Oxygen Evolution Reactivity of WO3

Abstract: WO3 is one of the most promising photocatalysts with a suitable energy band structure for water oxidation; however, the quick recombination of photoinduced charge carriers seriously limits the photocatalytic efficiency. Loading of suitable cocatalysts is considered as an effective method to significantly improve the photocatalytic activity. Herein, we used a facile one-step hydrothermal method and a “hydrothermal + photodeposition” method to synthesize xCo3O4/WO3 (x = 0.2, 0.4, 0.8) and yCoOOH/WO3 (y = 2, 3, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In general, certain classes of photocatalytic materials have their “preferred” scavenging solution where the resultant product yields are maximized due to the excellent scavenging abilities of the respective solutions. For example, thioacetamide (TEOA) as the best-in-slot (BIS) hole scavenger for the g-C 3 N 4 polymeric photocatalyst, Na 2 S/Na 2 SO 3 or AA as the BIS hole scavenger for sulfide-based photocatalysts in which one may provide better outcome over another depending on the cocatalysts used, Na 2 S 2 O 8 as an electron scavenger for ferrites such as NiFeO x and BiFeO 3 , , and AgNO 3 or FeCl 3 as the more generic go-to electron scavenger in many of the studies using the popular oxygen evolution photocatalysts, WO 3 and BiVO 4 . As the use of ZCS for oxygen evolution is rather scarce, the combination of ZCS and FeCl 3 as the photocatalyst–electron scavenger pair has most likely not been assessed before. Considering the occasion where FeCl 3 has great synergy with ZCS and can effectively draw away the photoexcited electrons in ZCS, this will leave a substantial amount of holes in the valence band (VB) of ZCS that can thus contribute to strong electronic absorption during ATR-FTIR assessment as evidently portrayed in Figure a,c.…”
Section: Resultsmentioning
confidence: 99%
“…In general, certain classes of photocatalytic materials have their “preferred” scavenging solution where the resultant product yields are maximized due to the excellent scavenging abilities of the respective solutions. For example, thioacetamide (TEOA) as the best-in-slot (BIS) hole scavenger for the g-C 3 N 4 polymeric photocatalyst, Na 2 S/Na 2 SO 3 or AA as the BIS hole scavenger for sulfide-based photocatalysts in which one may provide better outcome over another depending on the cocatalysts used, Na 2 S 2 O 8 as an electron scavenger for ferrites such as NiFeO x and BiFeO 3 , , and AgNO 3 or FeCl 3 as the more generic go-to electron scavenger in many of the studies using the popular oxygen evolution photocatalysts, WO 3 and BiVO 4 . As the use of ZCS for oxygen evolution is rather scarce, the combination of ZCS and FeCl 3 as the photocatalyst–electron scavenger pair has most likely not been assessed before. Considering the occasion where FeCl 3 has great synergy with ZCS and can effectively draw away the photoexcited electrons in ZCS, this will leave a substantial amount of holes in the valence band (VB) of ZCS that can thus contribute to strong electronic absorption during ATR-FTIR assessment as evidently portrayed in Figure a,c.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 2(i), the SAED pattern is clearly visible as monoclinic phases are formed in accordance with the crystal plane (002). 49 As can be seen in Figure 3 39,48 An X-ray photoelectron spectrometer (XPS) was used to determine the chemical structure and binding state of the Ru− Pd/WO 3 /MXene nanocatalysts. As can be seen in Figure 4 (a), the survey spectrum of Ru−Pd/WO 3 /MXene reveals the presence of Ti, W, Ru, Pd, N, C, and O elements.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Wu’s group summarized the common synthesis methodologies of metal oxide aerogels and their photocatalytic applications in water treatment, solar water splitting, and gas-chase reactions, including CO 2 reduction and CO oxidation . Wang and his co-workers employed Co 3 O 4 and CoOOH as the co-catalysts of WO 3 for photocatalytic O 2 production . It is revealed that the mixed valence of co-catalysts is more favorable for photocatalytic water oxidation.…”
Section: Photooxidationmentioning
confidence: 99%
“…25 Wang and his co-workers employed Co 3 O 4 and CoOOH as the co-catalysts of WO 3 for photocatalytic O 2 production. 26 It is revealed that the mixed valence of co-catalysts is more favorable for photocatalytic water oxidation. Zhang's group presented serpentine Ni 3 Ge 2 O 5 (OH) 4 nanosheets on porous Mo 2 N for an efficient oxygen evolution reaction.…”
Section: ■ Photooxidationmentioning
confidence: 99%